MORPHOLOGICAL AND CYTOLOGICAL CHARACTERISTICS OF INFLORESCENCE MUTANTS IN ALFALFA (MEDICAGO SATIVA L. SL). - Weigt, Dorota; Broda, Zbigniew; Lira, Jarosław; Mikołajczyk, Sylwia (Plant Breeding and Seed Science, 2009)
The presented study analyzed selected biometric characteristics of inflorescences, seed yield structure characters, and discussed cytological analyses concerning two spontaneous inflorescence mutants in alfalfa: top flowering (plants with the “tf”gene) and long peduncle mutants (plants with the “lp” gene). Analyses were conducted in 2005 and 2006 and the results were subjected to a one-way statistical analysis with the use of Tukey’s test...